2017
DOI: 10.3892/mco.2017.1444
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral and multiple mixed epithelial and stromal tumors of the kidney: A case report

Abstract: Mixed epithelial and stromal tumor (MEST) of the kidney is a benign tumor occurring predominantly in older women. Histologically, MEST comprises tubuloglandular and cystic structures in an ovarian-like stroma. Bilateral and multiple cases are rare. We herein present a case of bilateral and multiple MEST in a 43-year-old woman. The patient presented with gross hematuria and was referred to a primary care physician. A computed tomography scan revealed 5 tumors in the right and 2 in the left kidney. Renal cell ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 6 publications
0
21
0
1
Order By: Relevance
“…Due to this information it can be considered that hormones are a risk factor for this tumor. The clinical presentation of MEST is similar to typical renal tumor (1,2,(4)(5)6,8,(10)(11)(12). However approximately ¼ of known diagnosed MESTs were asymptomatic.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Due to this information it can be considered that hormones are a risk factor for this tumor. The clinical presentation of MEST is similar to typical renal tumor (1,2,(4)(5)6,8,(10)(11)(12). However approximately ¼ of known diagnosed MESTs were asymptomatic.…”
Section: Introductionmentioning
confidence: 81%
“…Current treatment strategy is based on surgical operation. Imaging studies usually reveal a cystic lesion with soft tissue components (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Microscopic findings consist of epithelium with mesenchymal tissue (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Minoda et al reported a patient who was diagnosed as having bilateral MESTK and underwent a left partial nephrectomy only and active surveillance of the right lesion ( 2 ). Our report shows that next generation sequencing cannot help guide further treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Cases in males are rarely reported, especially in teenagers. The female to male ratio is about 6:1, with the mean age being 46 years ( 2 ). Patients mainly present asymptomatically, but it is also possible that they present with flank pain, palpable abdominal mass, and hematuria.…”
Section: Introductionmentioning
confidence: 99%